Project – Based Learning: Facilitating the Development of Students’ Critical Thinking in English Essay Writing - Eva Fitriani Syarifah; Afief Fakhruddin; Eka Nurhidayat (ETERNAL (English Teaching Journal), 2023)
This study aimed to investigate how the project – based learning was implemented to facilitate the development of students’ critical thinking skills in English essay writing in higher education context. An exploratory case study research design was used in this study while the participants were one lecturer and 15 students. The data were gleaned from classroom observations, interview, and documents. The data analysis results that teaching English essay writing in which project- based learning was implemented covers three stages including preparation, implementation, and presentation. The other result from data analysis shows that the students can write essay cohesively and coherently in which this results indicates students’ critical thinking skills.  The results lead to the conclusion that all of the students had chance to be actively involved during the project and in teaching and learning prosess. It indicates that project – based learning apparently could facilitate the development of students’ critical thinking in English essay writing.